Challenges in biomass valorization by olefin metathesis - Del Vecchio, Antonio; Mauduit, Marc (Comptes Rendus. Chimie)
The production of biosourced intermediates from renewable raw materials represents a hot topic for the scientific community, which is engaged in the development of more efficient and sustainable processes. In this perspective, olefin metathesis (OM) is one of the best choices to address societal issues, harnessing the conversion of compounds extracted from plants into molecules of interest with a very low carbon footprint. The aim of this article is to highlight and discuss two relevant metathesis processes dedicated to biomass valorization (on the one hand, the transformation of feedstocks resulting from Fischer–Tropsch cuts of wood wastes, and on the other hand, the transformation of unrefined unsaturated fatty esters from sunflower oils) which involve highly efficient and selective ruthenium-based catalysts. The recent development of continuous flow Z-selective metathesis processes applied to the synthesis of biosourced odorant molecules and insect pheromones will also be discussed.